Small ruminants in the farming systems of coastal Kenya - Thorpe, W.R.; Nyambaka, R.; Chabari, F.; Maki, M. Ole; Rugema, E. (Research Inst. for Animal Husbandry, 1990)
The farming systems and particularly the livestock sub-systems of the coastal subhumid zone of Kenya are described by ILCA in collaboration with Kenya agricultural Research Institute (KARI) & Minstry of Livestock Development. Reports for sample area in Kilifi District indicates that while less than 10 percent of smallholder farms owned cattle, between 30 to 70 percent of farmers owned small ruminants. For more accuracy results are abstracted from systems surveys carried out in Kaloleni Division, Kilifi District by the KARI/ILCA Smallholder Dairy Project.